Correction: Banjac et al. The Effects of Different Doses of Sildenafil on Coronary Blood Flow and Oxidative Stress in Isolated Rat Hearts. Pharmaceuticals 2023, 16, 118 - Nada Banjac; Velibor Vasović; Nebojša Stilinović; Ana Tomas; Lucija Vasović; Nikola Martić; Dušan Prodanović; Vladimir Jakovljević (MDPI AG, 2024)
Prof [...]